Penggunaan Model Problem-Based Learning Untuk Meningkatkan Hasil Pembelajaran Tematik Terpadu di SDN 05 Sungai Beremas - Rizky Risnaldi; Arwin Arwin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2023)
The background of this research is the low learning outcomes of students and the inappropriate learning model used by the teacher. The purpose of this study was to describe and improve student learning outcomes in integrated thematic learning in class V SDN 05 Sungai Beremas using the Problem-Based Learning model. The type of research was Classroom Action Research using quantitative and qualitative methods. This research was conducted over two cycles: Planning, implementation, observation, and reflection are the research procedures. Observation, tests, and documentation are the data collection techniques. The class teacher and 24 students became the research subjects. The results showed an increase, as follows: 1) Cycle 1 lesson plan assessment amounted to 86.11%, cycle 2 amounted to 97.22%. 2) Cycle 1 assessment of teacher aspects amounted to 87.5%, and cycle 2 amounted to 96.42%. 3) Cycle 1 assessment of the learner aspect was 85.71%, and cycle 2 was 96.42%. 4) Cycle 1 assessment of knowledge and skills aspects amounted to 72.05%, and cycle 2 amounted to 82.4%. Thus, learning outcomes in class V SDN 05 Sungai Beremas can increase with the use of the Problem-Based Learning model.